PENGARUH CAPITAL INTENSITY RATIO, RECEIVABLE TURNOVER RATIO DAN EFFECTIVE TAX RATE TERHADAP STOCK RETURN PADA PT WASKITA KARYA (PERSERO) TBK PERIODE 2015–2024 - Mella Safitri; Jamaludin Jamaludin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the effect of Capital Intensity Ratio, Receivable Turnover Ratio, and Effective Tax Rate on the stock return of PT Waskita Karya (Persero) Tbk during the 2015–2024 period. The research adopts a quantitative approach with various analytical methods, including descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination analysis to measure the model’s ability to explain the dependent variable. The results show that the Capital Intensity Ratio has a negative and significant effect on stock return (t = -4.817; sig. 0.003 < 0.05). In addition, the Receivable Turnover Ratio also has a negative and significant effect on stock return (t = -4.591; sig. 0.004 < 0.05). On the other hand, the Effective Tax Rate has a negative but insignificant effect on stock return (t = -2.066; sig. 0.084 > 0.05). Simultaneously, all independent variables have a significant effect on stock return (F = 10.201; sig. 0.009 < 0.05). The coefficient of determination of 83.6% indicates strong explanatory power, while the remaining 16.4% is influenced by other factors outside this study.